SUPPLY CHAIN MANAGEMENT SUSTAINABILITY THROUGH THE PERFORMANCE IMPROVEMENT OF MTS-MTO PRODUCTION SYSTEM TYPOLOGY - RIZKI ANISSA (Politeknik APP Jakarta, 2017)
Batik has been acknowledged as a Masterpiece of Oral and Intangible Heritage of Humanity of Indonesia based on UNESCO in 2009 and this asset is considerably becoming the prospect to overcome global market in Asia. In the other side, the global competition can only be encountered by sustainably developing the internal industry. Therefore, this research elaborates sustainable supply chain performance assessment and also the improvement framework applied in Batik industry with MTO-MTS typology. For fulfilling the provisions of sustainability, the economic, environmental, and social is strictly important to be involved in. Supply Chain Operations Reference (SCOR) is a reference model of assessment considering five attributes to be measured and implemented as the perspective of economic assessment. Employee's welfare and liquid waste assessment are then becoming the method to measure the social and environmental aspect. This resulted score as: Reliability is 89.24%, Responsiveness for MTS is 96% for MTO is 62%, Cost is 83.32%, Agility is 100%, and the Assets Management is 79.63%. For the social aspect, the score of parameter Health Insurance is 100%, Safety Tools is 100%, Basic Allowance is 70%, Annual Allowance is 100%, Appropriate Work Hours is 67%, and the Reward is 70%. For the environmental aspect, the temperature is 100%, pH 62.0%, BOD 100%, COD 64.7%, and TSS 7.4%. The improvement framework is also proposed by using Customer Order Decoupling Point (CODP) that results the increased performance in the Responsiveness attribute in the MTO process as much as 8.25%.